Aggressive Digital Papillary Adenocarcinoma of the Hand Presenting as a Felon - Justin R. Bryant; Preston Gardner; Matthew Yousif; John C. Pui; Raymond T. Hajjar; E. Aron Haass (Case Reports in Orthopedics)
Aggressive digital papillary adenocarcinoma is a rare eccrine sweat gland malignancy that is frequently misdiagnosed at initial presentation. Histologically, this tumor is similar in appearance to many adenocarcinomas and as such may be diagnosed as a metastatic lesion. We present the case of a patient with digital papillary adenocarcinoma, which was initially diagnosed as a felon. No consensus has been published regarding the treatment of this disease. A review of the diagnosis, pathology, treatment, and adjunctive treatments of aggressive digital papillary adenocarcinoma are also included.